Efektivitas Rencana Pembelajaran Semester (RPS) berbasis OBE Pada Mata Kuliah Agama Islam di Universitas Bengkulu - Gusti, Ririn; Rohimin; Qolbi Khoiri; Nurlaili (Jurnal Pendidikan Indonesia, 2025)
The Outcome-Based Education (OBE) approach is applied to improve active engagement and student learning outcomes that are still limited in the traditional curriculum. The development of OBE-based RPS with MBKM integration is a potential solution to improve the quality of education. This study aims to analyze the effectiveness of OBE-based RPS in improving cognitive learning outcomes, learning activities, and student soft skills. This study used a quasi-experimental method with control and experimental groups. The experimental group applied OBE-based RPS and while the control group applied conventional RPS. The subjects of this study amounted to 40 college students. Data were collected through observation, questionnaires, and learning outcome tests. The results showed that the experimental group achieved a 96% completion rate, much higher than the control group which only reached 64%. The project-based learning model and problem solving applied to the experimental group were also proven to improve creativity, soft skills, and student learning outcomes. The OBE-based RPS proved effective in improving cognitive, psychomotor, affective learning outcomes and student competencies. Project-based learning and problem solving strengthen students' activities and involvement in the learning process, and prepare them to face global challenges. The OBE-based RPS proved to be more effective than the conventional RPS in improving students' learning outcomes, cognitive, psychomotor, and affective skills.